2020
DOI: 10.1177/0269216320981713
|View full text |Cite
|
Sign up to set email alerts
|

Preplanned participation of paramedics in end-of-life care at home: A retrospective cohort study

Abstract: Background: Paramedics commonly face acute crises of patients in palliative care, but their involvement in end-of-life care is not planned systematically. Aim: To evaluate a protocol for end-of-life care at home including pre-planned integration of paramedics and end-of-life care wards. Design: Paramedic visits to patients in end-of-life care protocol were retrospectively studied. Setting/Participants: All of the patients who had registered for the protocol between 1 March 2015 and 28 February 2017 in North Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
77
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(82 citation statements)
references
References 27 publications
1
77
0
Order By: Relevance
“…40 These findings were supported by a retrospective cohort study evaluating paramedic attendance of patients with an end-of-life protocol. 36 However, despite many participants expressing concern over the level of suffering a palliative patient endures when undergoing life-prolonging treatment and transportation to hospital, four studies highlighted professional repercussions and fear of litigation as major barriers affecting a paramedic’s ability to move beyond hospital-oriented care. 20,26,27,29 Other studies explored this further, recognising the ethical dilemma and apprehension paramedics face when resuscitating a palliative care patient – a default procedure in many clinical practice guidelines – and expressed a strong desire to facilitate natural death despite often lacking the legal latitude.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…40 These findings were supported by a retrospective cohort study evaluating paramedic attendance of patients with an end-of-life protocol. 36 However, despite many participants expressing concern over the level of suffering a palliative patient endures when undergoing life-prolonging treatment and transportation to hospital, four studies highlighted professional repercussions and fear of litigation as major barriers affecting a paramedic’s ability to move beyond hospital-oriented care. 20,26,27,29 Other studies explored this further, recognising the ethical dilemma and apprehension paramedics face when resuscitating a palliative care patient – a default procedure in many clinical practice guidelines – and expressed a strong desire to facilitate natural death despite often lacking the legal latitude.…”
Section: Resultsmentioning
confidence: 99%
“…17,21,22,2426,28,3032,34,3841 Notably, in one study hospital-based death was reported for 54% of 252 patients in areas where paramedics did not have access to 24/7 palliative home care services, in comparison to 33% in areas where these services were available. 36 Paramedic length of service and end-of-life experience appeared to be other key factors facilitating paramedic confidence to treat a palliative patient. 22…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations